Stenotrophomonas maltophilia: a serious and rare complication in patients suffering from burns. - Dalamaga, Maria; Karmaniolas, Konstantinos; Chavelas, Charilaos; Liatis, Stavros; Matekovits, Helen; Migdalis, Ilias (Burns, 2003)
Stenotrophomonas maltophilia is rarely implicated in clinical infections but it constitutes a significant nosocomial pathogen, especially in immunocompromised patients. This report describes the first case of a generalised infection caused by S. maltophilia that included bacteremia, wound and respiratory tract infection in a patient suffering from burns. Given the emergence of S. maltophilia nosocomial infections, especially in patients with burns, isolation of the bacterium from blood cultures should prompt the commencement of adequate antibiotic treatment.
Keywords: Burns; Cross Infection; Gram-Negative Bacterial Infections; Humans; Male; Middle Aged; Opportunistic Infections; Stenotrophomonas maltophilia